2017
DOI: 10.1038/s41598-017-15761-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics identifies metabolite biomarkers associated with acute rejection after heart transplantation in rats

Abstract: The aim of this study was to identify metabolite biomarkers associated with acute rejection after heart transplantation in rats using a LC-MS-based metabolomics approach. A model of heterotopic cardiac xenotransplantation was established in rats, with Wistar rats as donors and SD rats as recipients. Blood and cardiac samples were collected from blank control rats (Group A), rats 5 (Group B) and 7 days (Group C) after heart transplantation, and pretreated rats 5 (Group D) and 7 days (Group E) posttransplantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…D-glutamine exhibited good diagnostic capability for the diagnosis of the early acute rejection after heart transplantation with a high sensitivity and specificity. 38 Moreover, inhibition of glutamine metabolism was considered to prevent graft rejection by inhibiting generation and function of effector T cells. In fully mismatched skin and heart allograft transplantation models, the inhibitor of glutamine metabolism 6-diazo-5-oxo-L-norleucine (DON) combined with the glycolytic inhibitor 2-deoxyglucose (2-DG) and the anti-type II diabetes drug metformin, were demonstrated to prevent or delay graft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…D-glutamine exhibited good diagnostic capability for the diagnosis of the early acute rejection after heart transplantation with a high sensitivity and specificity. 38 Moreover, inhibition of glutamine metabolism was considered to prevent graft rejection by inhibiting generation and function of effector T cells. In fully mismatched skin and heart allograft transplantation models, the inhibitor of glutamine metabolism 6-diazo-5-oxo-L-norleucine (DON) combined with the glycolytic inhibitor 2-deoxyglucose (2-DG) and the anti-type II diabetes drug metformin, were demonstrated to prevent or delay graft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al (2017) recently used a heterotopic HTx rat model to determine the metabolic profile post-BSD in serum. 136 They found a panel of 4 metabolites, D-tagatose, choline, C16 sphinganine and D-glutamine, could accurately diagnose early rejection.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Future studies profiling these changes in myocardium and biofluids with thorough biochemical techniques (eg metabolomics, magnetic resonance imaging), across acute and chronic post-HTx stages are necessary to ascertain therapeutic targets and the metabolic state of the transplanted heart. Targeting aberrant signalling, altering metabolic function (as in those studies on HF 35 ) or identifying risk of graft failure via metabolic biomarkers such as those identified by Lin et al 136 , or the panel of metabolites identified in liver 10 and kidney transplant 11,12 studies, may thus improve patient outcomes.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Moreover, MS can also be combined with chromatographic methods (LC or GS) to improve metabolite separation. These technologies allow the investigation of metabolic changes in disease models and organ physiology, including Tx [ 23 ].…”
Section: Introductionmentioning
confidence: 99%